Implikasi Erupsi Gunung Agung Terhadap Sosial Ekonomi Pelaku Pariwisata di Kelurahan Ubud, Kecamatan Ubud, Kabupaten Gianyar,Bali - I Kadek Diana Putra; Luh Putu Kerti Pujani (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Mount Agung eruption has a significant influence on the tourism sector. The tourism sector becomes the main sector of the Ubud community. This study aims to determine the implications of Mount Agung eruption on socio- economic tourism actors in the village of Ubud in the accommodation and restaurant business. This research is important to do because it is useful for tourism actors who are directly involved in the tourism sector so that it can deal with natural phenomena that unpredictable events occur. The research method in this report is using qualitative and quantitative data types. Sources of data used are primary and secondary data. Data collection techniques used are observation, interview, and documentation. Informant determination technique used is purposive sampling. Data analysis used is descriptive qualitative. The first thing to do is to observe for social phenomena and then to categorize the information obtained, then explain the categorization, then explain the categorization relationship and draw the general conclusion. The results of this research indicate that the implications of the Gunung Agung eruption on socio-economic tourism actors in Ubud Village include occupation of accommodations, restaurant visits, shortening employee work hours, employee income, employee welfare, family employee education investment, additional employee work that work in accommodation restaurant business. Keywords: Implication of Eruption, Social Economy, Tourism Actors